Potentialities and challenges of the Multiprofessional Residency Program for the training of nurses working in Primary Health Care (Research, Society and Development, 2020)
Multiprofessional Residencies were created with the aim of qualifying professionals to act in accordance with the Unified Health System. Thus, the objective of this article is to report on the potential and challenges of the Multiprofessional Residency Program for the training of nurses working in Primary Care. This is a descriptive study that comes from an experience report of resident nurses from the Multiprofessional Residency Program in Family and Community Health (RMSFC) of the State University of Piauí, the result of a process of experiences and critical reflections on pedagogical practices, assistance and health education offered in Basic Health Units, in the municipality of Teresina, Piauí. The RMSFC consists of modules, multiprofessional extension projects and category extension projects, in which practices related to public health were experienced. The categories highlighted in the article deal with: Multiprofessional Residence as a space for multidisciplinary and interprofessional articulation; Active methodologies as facilitating strategies for health promotion; and Multiprofessional Residency as a place of care practice and improvement of technical and scientific skills in the Health Care Network. It is concluded that the experience as residents contributed to the formation of critical and reflective attitudes, as well as enabled active participation in processes centered on health, health promotion, focusing on the emancipation of users under the aegis of the expanded clinic and the qualification of access.